Learning Factories 4.0 in technical vocational schools: can they foster competence development? - Roll, Michael; Ifenthaler, Dirk (Empirical Research in Vocational Education and Training, 2021)
Learning Factories 4.0 are thought to prepare vocational students for the challenges of Industry 4.0. The implementation of those interconnected Learning Factories 4.0 at technical vocational schools may promote the development of subject-related technical competencies as well as multidisciplinary digital competencies. Still, research is scarce with regard to the development of competencies supported through Learning Factories 4.0 in technical vocational schools. Hence this research focusses on subject-related technical and multidisciplinary digital competencies of technical vocational students change due to different levels of Learning Factory 4.0 interaction over time. Three subsequent competence tests with N = 63 technical vocational students were conducted. Findings indicate the benefits of integrating Learning Factories 4.0 for developing subject-related competencies in technical vocational schools. However, the study could not identify a positive development of multidisciplinary digital competencies. The findings of this study can help educators to further develop learning environments with support from Learning Factories 4.0 as well as preparing their learners for the demanding competencies of Industry 4.0.